LOW SALINITY WATER INJECTION EVALUATION AND MATURE FIELD DEVELOPMENT AT ANGGORO SHALLOW SAND, SANGASANGA FIELD - Dani Novriyandi (Journal of Petroleum and Geothermal Technology, 2024)
AbstractAnggoro's shallow sand was perforated at well ANG-1033 (D4-N1 layer). Oil production in this well increased from an average of 15 BOPD to 170 BOPD. That the perforated layer was affected by low salinity water injection (salinity < 3000 ppm). Evaluation of water injection sweep efficiency was carried out using the Dykstra-Parson method, vertical efficiency of about 0.3, area efficiency of 0.7, and displacement efficiency of 0.3. The Estimated Ultimate Recovery (EUR) of this well provides is 197 MBbls with an additional RF of around 20 %. This increase is due to the low salinity water injection sweep mechanism that occurs. The clay content plays an important role in the mechanism that occurs in this layer, these mechanisms fines migration, increase in pH, multi ion exchange, double layer effect, and salting in which these mechanisms result in increased oil recovery. Seeing the production results from the D4-N1 layer and oil production in this layer can still be maximized, in the future this layer can be developed with several programs such as reactivation, workover, and development drilling.Keywords: Low salinity water injection, shallow layer, efficiency